ANALISIS PERILAKU MORAL ANAK DI LABORATORIUM PAUD FKIP UNIVERSITAS RIAU USIA 5-6 TAHUN - Handayani, Priti Oktari; Chairilsyah, Daviq; Zulkarnain, Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research aims to determine the mutually respectful behavior ofchildren aged 5-6 years in the PAUD Laboratory, Fkip, Riau University. The researchsubjects were 35 children aged 5-6 years. Based on the research results, it is known thatthe average score obtained by children aged 5-6 years at the Early ChildhoodEducation Laboratory Fkip Riau University was 11.69 if the percentage was 77.90% inthe Good category. This shows that the moral behavior of children aged 5-6 years at theEarly Childhood Education Laboratory Fkip Riau University has developed well.Furthermore, based on the chi-square test of 20.818, which is greater than the chisquare table of 3.841 (20.818>3.841) and the significance obtained is 0.000, which issmaller than 0.05 (0.000<0.05), it can be concluded that there is an influence of genderon moral behavior. children aged 5-6 years at the Early Childhood EducationLaboratory, Fkip, Riau University. Based on the Contingency Coefficient test of 0.611.Then the coefficient of determination KD = R2 X 100%, KD = 0.6112 X 100% =37.33%. This shows that gender has an influence on the moral behavior of childrenaged 5-6 years at the Early Childhood Education Laboratory Fkip Riau University by37.33% and the remaining 62.97% is influenced by other factors.Keywords: Analysis, Moral Behavior, Children Aged 5-6 Years